IDENTIFIKASI SAMPAH LAUT MAKRO DI PANTAI LE GRANDEUR KOTA BALIKPAPAN KALIMANTAN TIMUR - Ardan Ardan; Akhmad Rafi’i; Ghitarina Ghitarina (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
There is a lot of waste that is difficult to decompose and accumulates in nature, especially at the coastal and ocean, resulting in environment disturbance. This study was aimed to identify macro-size marine debris collected from Le Grandeur beach, Balikpapan City, East Kalimantan. A 100 x 20 m transect line was set at the beach. Each transect equipped with 5x5 m subtransect where the macro-debris was sampled. All debris in subtransect were collected and were cleaned prior sorted and grouped based on their categories namely plastic, glass, metal, rubber, wood and other types. Samples from each type were counted and measured in weight. Based on the results of the study, samples of macro marine debris collected at the study site were plastic, glass, metal, rubber, wood and others with a total debris of 435 items and total weight of 2,263.772 g/m2. Total density of waste is 86.6 particles/m2 with the percentage of each waste being 45% plastic, 0% glass, 2% metal, 2% rubber, 2% wood and 49% others.